Site use and connectivity of female grey seals (Halichoerus grypus) around Wales - Izzy Langley; Tobias Rosas da Costa Oliver; Lex Hiby; Thomas B. Stringell; Ceri W. Morris; Oliver O’Cadhla; Lisa Morgan; Kate Lock; Sarah Perry; Stephen Westcott; Dave Boyle; Birgitta I. Büche; et al. (Marine Biology, 2020)
Grey seals ( Halichoerus grypus ) are a qualifying feature of three special areas of conservation (SACs) in Wales, yet relatively little is known of their site use along this coastline. Since 1992, many individuals and organisations have contributed to a grey seal photographic identification database held by Natural Resources Wales, which is one of the largest and oldest of its kind, providing key information from grey seal haul-out sites around the Celtic and Irish Seas. Here, we investigated spatial connectivity of haul-out sites and fidelity of adult females to breeding sites. The minimum number of adult female grey seals using the area between 1992 and 2016 was 2688. Individual capture histories and relative spatial transition probabilities ( P ij ) between pairs of location groups were calculated. Adjacent locations were highly connected (e.g. Lleyn Peninsula and Bardsey, P ij = 0.7) but connections spanned the entire region, up to 230 km apart (e.g. Skomer and Dee Estuary, P ij = 0.004). Resights were recorded within SACs (e.g. Lleyn Peninsula and Bardsey [Lleyn Peninsula and the Sarnau SAC], P ij = 0.7), between SACs (e.g. Bardsey and Skomer [Pembrokeshire Marine], P ij = 0.03), between SACs and non-designated areas (e.g. Skerries and Bardsey, P ij = 0.09) and between sites outside any protected area (e.g. Dee Estuary and Anglesey, P ij = 0.5). While inter-annual fidelity to breeding sites was high ( P ij = 0.82–1), individual female grey seals moved throughout the region. This evidence of extensive site use beyond protected areas is important for the management and conservation of grey seals around Wales.